An educational module to explore CRISPR technologies with a cell-free transcription-translation system. Issue 1 (21st January 2019) - Collias, Daphne; Marshall, Ryan; Collins, Scott P; Beisel, Chase L; Noireaux, Vincent
Abstract: Within the last 6 years, CRISPR-Cas systems have transitioned from adaptive defense systems in bacteria and archaea to revolutionary genome-editing tools. The resulting CRISPR technologies have driven innovations for treating genetic diseases and eradicating human pests while raising societal questions about gene editing in human germline cells as well as crop plants. Bringing CRISPR into the classroom therefore offers a means to expose students to cutting edge technologies and to promote discussions about ethical questions at the intersection of science and society. However, working with these technologies in a classroom setting has been difficult because typical experiments rely on cellular systems such as bacteria or mammalian cells. We recently reported the use of an E. coli cell-free transcription-translation (TXTL) system that simplifies the demonstration and testing of CRISPR technologies with shorter experiments and limited equipment. Here, we describe three educational modules intended to expose undergraduate students to CRISPR technologies using TXTL. The three sequential modules comprise (i) designing the RNAs that guide DNA targeting, (ii) measuring DNA cleavage activity in TXTL and (iii) testing how mutations to the targeting sequence or RNA backbone impact DNA binding and cleavage. The modules include detailed protocols, questions for group discussions or individual evaluation, and lecture slides to introduce CRISPR and TXTL. We expect these modules to allow students to experience the power and promise of CRISPR technologies in the classroom and to engage with their instructor and peers about the opportunities and potential risks for society.